Crowdsourcing and the Architectural Competition as Organisational Technologies - Andreas Kamstrup (Copenhagen Business School (CBS), 2017)
In this dissertation, I take interest in crowdsourcing and architectural competitions as I focus on examining how a crowdsourcing platform works in the building industry and how the practices unfolding on it relates to – and maybe mimics – architectural competitions. The platform is operated and situated in the building industry, where `the architectural competition' stands as an institution for how to coordinate interactions between actors. I also take interest in an architectural competition setup where dialogue between architects and jury is part of the setup. In overall terms, the research project aims to contribute to understanding novel interaction practices in the building industry and the architectural world at large. The research is based primarily on ethnographic explorations and the results hereof is the article-based dissertation you have just embarked on. The dissertation is structured in two parts, where the first contains most of the framework and plays the role of an extended reading guide to the three articles presented in the second part, which also contains the conclusion.
hdl:10398/9561
Keywords: 650